The challenges of the Internet of Things (IoT) in the context of construction cost management - Jamlus, Nur Dini Farzana; Che Haron, Roziha (IIUM Press, 2024)
The construction industry faces significant challenges related to cost overruns, project delays, and inefficiency. Traditional cost management methods rely on manual processes and limited data sources, but the advent of technology and the Internet of Things (IoT) offers innovative solutions. This research explores the application of IoT in construction cost management, starting with a literature review that highlights the limitations of current methods and areas where IoT can enhance value. The study aims to identify IoT applications and challenges in construction cost management. It employs a mixed-method approach, including a questionnaire survey of 47 respondents and interviews with four construction stakeholders. The research finds that IoT sensors provide real-timedata, addressing historical inefficiencies and improving project outcomes. However, it also reveals challenges such as additional budget for acquiring IoT technologies and poor collaboration among construction parties. In summary, IoT promisesto transform construction cost management but requires addressing budgetary and collaboration issues to maximize its potential.